Spiritual value education in shaping student nationalism: evidence from Indonesian Islamic schools - Frimayanti, Ade Imelda (UIR Press, 2026)
Nationalism is a crucial aspect of character development among Indonesian students, particularly amid globalization, digital culture, and transnational values that may weaken patriotic attitudes and national commitment. Schools play a strategic role in fostering nationalism through character education, including spiritual value education that emphasizes moral awareness, ethics, self-control, social responsibility, and universal values. Although previous studies have widely examined character education, civic education, and nationalism, limited empirical research has directly investigated the influence of spiritual value education on student nationalism, especially through a quantitative approach in Islamic school contexts. Addressing this gap, this study aims to examine the effect of spiritual value education on student nationalism. The novelty of this study lies in positioning spiritual value education as a specific predictor of student nationalism rather than merely as a component of general character education. This study employed a quantitative survey method involving 120 students from MTs Negeri 1 Lampung Selatan and MAN 1 Bandar Lampung. Data were collected using structured questionnaires and analyzed through simple linear regression and Pearson correlation analysis. The findings show that spiritual value education has a positive and significant effect on student nationalism, contributing 73.2% to its development. Theoretically, this study contributes to character education and civic education literature by highlighting spiritual value education as a foundation for strengthening nationalism. Practically, the findings imply that schools, teachers, and policymakers should integrate spiritual values more systematically into learning, school culture, and character-building programs. This study is limited to two Islamic schools in Lampung; therefore, broader studies across different educational contexts are recommended.